Fasting Meets the Forecast: Thermal Conditions Influence Post-Mortem Muscle Traits in Rainbow Trout (Oncorhynchus mykiss) - Andrea Martínez Villalba; Álvaro De la Llave-Propín; Jesús De la Fuente; Elisabet González de Chavarri; María Teresa Díaz; Montserrat Fernández-Muela; Almudena Cabezas; Roberto González-Garoz; Morris Villarroel; Rubén Bermejo-Poza (Fishes)
In aquaculture, pre-slaughter fasting reduces stress and improves muscle quality. Fasting periods of 55–58 degree days (°C d) enhance muscle structure and post-mortem biochemistry in rainbow trout (Oncorhynchus mykiss), although optimal durations vary with temperature. This study investigated the effects of fasting from none to extended durations on 495 rainbow trout under summer (22 °C) and winter (8 °C) conditions. In summer, elevated temperatures increased muscle glycogen, leading to lower pH and delayed rigor mortis (RM), especially in fasted groups, where RM peaked at 24 h post-mortem. In winter, RM occurred earlier. Prolonged fasting increased acetylcholinesterase (AChE) activity, with high baseline levels in non-fasted summer fish. Muscle lightness at 0 h post-mortem was highest in non-fasted winter fish but declined to summer levels in fasted groups. Antioxidant enzyme activity (glutathione-S-transferase, glutathione peroxidase) increased with fasting in winter, while summer heat masked responses. The expression of genes for mineralocorticoid receptors and heat shock proteins remained stable in warm conditions. Summer delayed metabolic decline due to higher glycogen-triggered excessive AChE activity from heat stress. Winter supported faster metabolic adjustment and more regulated enzyme activity. These findings highlight the need to adjust fasting strategies seasonally to optimize muscle traits, especially under thermal variations.